Heart Disease Prediction Using Machine Learning - Lingala Rajeswar Reddy,; Gogula Hari Bhanu Prasanth,; Raghavendra K,; Sunkara VenkatGirish,; Dr. P VijayaKarthik, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
The prediction using the alloy of clinical data. The exists of the heart disease of prediction using for the data of age, sex, chest pain, trestbps. For medical purposes, the heart sickness is use of difficult ventures. We develop the neural network of clinical features of data. For medical, purpose of the heart sickness of the data. A known range of available datasets leads to numerous options with the help of analyzing visual analytics.
Keywords: Clinical Data; Visual Analytics; Machine Learning